Penguatan Pendidikan Karakter Religius Siswa Berbasis Manajemen Kelas - Liantika Permatasari; Muhlasin Amrullah; Mahardika Darmawan Kusuma Wardana (Fitrah: Journal of Islamic Education, 2023)
The problem of character education is a common problem until now, there are two models for strengthening character, namely inside the classroom and outside the classroom. This study aims to analyze the strengthening of classroom management-based character education, with a research focus on implementation and the constraints encountered. This research was conducted at SDN Celep Sidoarjo. This study uses phenoenology-based qualitative research methods, with data collection techniques of observation, interviews, and documentation studies as data collection tools. The results of this study indicate that the implementation of class-based religious character education through class management is carried out with a class agreement program, class control and classroom arrangement that has been integrated with religious character. Obstacles in the implementation of class-based religious character education through classroom management are violations of class agreements and habits in the classroom control program and lack of attention from parents. To overcome these obstacles the teacher gives punishment to students who violate it and coordinates with parents of students. The implication of this research is through the implementation of strengthening religious character education at SDN Celep Sidoarjo the learning objectives can be achieved and can improve religious character.